A melamine-based organic–inorganic hybrid material revealing excellent optical performance and moderate thermal stability. Issue 23 (1st June 2021) - Liu, Lehui; Bai, Zhiyong; Hu, Lei; Wei, Dongshan; Lin, Zhoubin; Zhang, Lizhen
Abstract : An ultraviolet organic–inorganic nonlinear optical material benefited from organic π-conjugated [C3 N6 ] groups and inorganic [ZnNCl3 ] groups, revealing excellent optical performance and moderate thermal stability. Abstract : Organic–inorganic hybrid nonlinear optical (NLO) materials have drawn increasing attention, and incorporate the suitable physicochemical characteristics of inorganic compounds with the excellent optical performance of organic molecules. Herein, a novel melamine-based organic–inorganic hybrid material, (H7 C3 N6 )·(H6 C3 N6 )ZnCl3 (1 ), was successfully synthesized by using (H7 C3 N6 ) + as a structure building block and introducing d 10 configuration metal Zn 2+ . Compound 1 has a large SHG response (2.8 × KDP), a high birefringence (Δ n = 0.255@1064 nm), a short cutoff edge (236 nm), and moderate thermal stability (250 °C), demonstrating its potential as an applicable ultraviolet (UV) NLO material. This finding may pave the way for new NLO materials with targeted properties.